The autonomic balance predicts cardiac responses after the first dose of fingolimod. (February 2015) - Rossi, S; Rocchi, C; Studer, V; Motta, C; Lauretti, B; Germani, G; Macchiarulo, G; Marfia, GA; Centonze, D
Background: Predictive markers of cardiac side effects would be helpful for the stratification and individualized monitoring of multiple sclerosis (MS) patients prescribed with fingolimod. Objective: To test whether the autonomic balance predicts a cardiac response after the first dose of fingolimod. Methods: A total of 55 consecutive relapsing–remitting MS (RRMS) patients underwent 'head-up tilt', Valsalva maneuver, deep breathing and handgrip tests before their first dose of fingolimod. The normalized unit of the high frequency (HF) component (HF normalized units; HFnu), reflecting mostly vagal activity; and the low frequency (LF) component (LF normalized units; LFnu) reflecting mostly sympathetic activity, were considered for the analysis of heart rate (HR) variability. The patients' HR and electrocardiographic parameters ((the interval between P wave and ventricular depolarization (PR); the interval between Q and T waves (QT)) were recorded during 6-hour post-dose monitoring. Results: We found significant correlations between measures of parasympathetic function and fingolimod-induced bradycardia. Subjects with higher Valsalva ratio and HR variation during deep breathing had, in fact, nadir HR ≤ 50 beats/minute (bpm) after the first fingolimod dose. Conversely, significant negative correlations were found between measures of sympathetic function and fingolimod-induced PR interval increase. Subjects with lower LFnu at rest and less increase of blood pressure on the handgrip test showed a PR interval increase > 20 ms after fingolimod. Conclusions: Assessing autonomic control of cardiovascular functions can be useful to predict cardiac effects after the first fingolimod dose.